A content analysis of sexual health and substance use information presented on study abroad websites: Findings and recommendations. Issue 6 (18th August 2019) - Marcantonio, Tiffany L.; Swirsky, Jill; Angelone, D. J.; Joppa, Meredith; Jozkowski, Kristen N.
Abstract: Objective : Despite study abroad students frequently engaging in risky behaviors, there is a dearth of research exploring prevention efforts taken by study abroad programs. The goal of this project was to examine information presented on study abroad program websites regarding sexual assault, alcohol use, drug use, and risky sexual behavior.Participants: A total of 753 universities in the US were selected from the Carnegie Classification of Institutes database.Method: Coders evaluated the website of each institution's study abroad program for the presence of information about the four factors of interest.Results: Sixty-seven percent of the websites provided no information on any of these risk behaviors. Chi-square analyses revealed institutional demographic differences in the presentation of prevention information. We also identified three emerging themes about avenues for modifying website content.Conclusion: Study abroad programs can provide more detail and action oriented information on their websites for students.